BEBERAPA MACAM PERLAKUAN TERHADAP PENYADAPAN AGATHIS SPP. UNTUK MENINGKATKAN BASIL GETAH - Dulsalam Dulsalam; Ishak Surnantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
An investigation into tapping of Agathis spp. using several methods has been carried out in Malang Forest District, Unit II Perum Perhutani, East Java, in 1983. The methods are designed to increase resin yield per unit time by manipulating tapping time, duration and covers and orientation.The investigation reveals that:1. Average resin production of the Agathis spp. for one week to two weeks times using of black and white plastic covers are respectively 9,85 gram/tree and 9,61 gram/tree. Without plastic cover the yield is 7, 76 gram/tree, shightly lower then when they are covered.2. The application of black plastic cover at tapping his significantly increased the yield up to 26,9% and those covered with white plastic of 23,8